An importance-performance analysis of international visitors to Penang, Malaysia - Omar, Shida Irwana; Muhibudin, Masitah; Sim, Jason Kok Jiun; Mohamed, Badaruddin (2013)
As one of the leading tourism destinations in Malaysia particularly after Kuala Lumpur and Pahang, Penang faces competition with its neighbouring competitors. To remain competitive, Penang needs to identify its strengths and weaknesses and consequently develop its future marketing strategies to secure high tourists’ satisfaction. Indeed, tourist satisfaction needs to be measured and monitored. In light of this consideration, it is believed that the importanceperformance analysis (IPA) was found to be a practical and useful technique for evaluating attributes that satisfy tourist and at the same time measure the importance of the same attributes to the tourists. This paper presents an application of the IPA technique to a sample of 372 international visitors who visiting Penang Island between September to October 2012. The data, analyzed quantitatively using matrices, showed the mean score of importance, which were plotted against performance onto two-dimensional axis. Results show that Penang performs well in five items namely (1) safety and security; (2) image of destination; (3) variety of attractions; (4) value for money; and (5) accessibility to the destination. On the other hands, findings show that there is room for improvement for accommodation services, and other areas like friendliness of the people and cultural/historical uniqueness appear to get too much attention. Moreover, this study is significant in identifying the prime market segments and evaluating the products and services provided. As a result, it provides an insight for tourism stakeholder such as hotels operators, public transport operators, food operators, policy makers and others towards enhancing future development of tourism in Penang.